Urinary volatile organic compound metabolites and reduced lung function in U.S. adults. (December 2022) - Mendy, Angelico; Burcham, Sara; Merianos, Ashley L.; Mersha, Tesfaye B.; Mahabee-Gittens, E. Melinda; Chen, Aimin; Yolton, Kimberley
Abstract: Background: Volatile organic compounds (VOCs) are associated with adverse respiratory outcomes at high occupational exposures. However, whether exposure levels found in the general population have similar effects is unknown. Methods: We analyzed data on 1342 adult participants in the 2011–2012 National Health and Nutrition Examination Survey aged ≥18 years old who had urinary VOC metabolites and spirometry measurements available. Linear regression models adjusting for covariates were fitted to estimate the associations of VOC exposures levels and spirometry outcomes, while accounting for survey design and sampling weights to generate nationally representative estimates. Results: The urinary metabolites for xylene, acrylamide, acrolein, 1, 3-butadiene, cyanide, toluene, 1-bromopropane, acrylonitrile, propylene oxide, styrene, ethylbenzene, and crotonaldehyde in our analysis were all detected in >75% of participants. Forced expiratory volume in 1 s (FEV1 ) to forced vital capacity (FVC) ratio % was lower with urinary metabolites of acrylamide (β: −2.65, 95% CI: −4.32, −0.98), acrylonitrile (β: −1.02, 95% CI: −2.01, −0.03), and styrene (β: −3.13, 95% CI: −5.35, −0.90). FEV1 % predicted was lower with the urinary metabolites of acrolein (β: −7.77, 95% CI: −13.29, −2.25), acrylonitrile (β: −2.05, 95% CI: −3.77, −0.34), propylene oxide (β: −2.90, 95% CI: −5.50, −0.32), and styrene (β: −4.41, 95% CI: −6.97, −1.85). Conclusions: This is the first study of a representative sample of the U.S. adult population to reveal associations of acrylonitrile, propylene oxide, and styrene urinary metabolites with reduced lung function at non-occupational exposures. Results also support previous evidence of acrylamide and acrolein's association with adverse respiratory outcomes. Highlights: We examined the association of urinary volatile organic compound metabolites with lung function in a sample representative of the US adult population. Urinary metabolites of acrylamide, acrylonitrile, and styrene were associated with lower FEV1/FVC ratio. Urinary metabolites of acrolein, acrylonitrile, propylene oxide, and styrene were associated with lower FEV1 % predicted. The associations of urinary volatile organic compounds metabolites with lower lung function were independent of smoking.